Изменчивость частоты апомиксиса и половой структуры в популяциях Antennaria dioica европейской части России - Кашин, А.С.; Кочанова, И.С.; Лисицкая, Н.М.; Угольникова, Е.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. 13 populations of A. dioica, growing in Saratov, Penza, Ulyanovsk, Kirov Regions and the Republic of Chuvashia, Mari-El, Komi were studied to identify apomixis rate variability and sex structure along a gradient of geographical coordinates (51°30' NL, 45°30' EL – 60°00' NL, 49°30' EL). Methods. Frequency of apomixis was diagnosed on the basis of comparative data on seed production of plants in the free pollination and flowering pollenless mode, as well as featured cytoembryologically. For cytoembryological analysis inflorescences were fixed 1–3 days before flowering in the latch Clark. The enlightening liquid Guerra (Herr, 1971) was used to enlighten ovules. Methodology of preparation of "enlightened" ovules was modified by us. Results. The frequency of apomixis and sex structure of populations of Antennaria dioica were studied in the European part of Russia on the gradient of latitude. It was shown that closer to the southern and northern boundaries of the range plants A. dioica behave as obligatory amfimictic, while in the central part of the area – as facultatively apomictic. It was revealed that under arid conditions in the southern regions a year after a drought flowering of A. dioica plants is completely suppressed, and in regions with the less arid climate the balance of flowering plants shifts towards "male" individuals. Relatively dry conditions of the previous before the flowering year led to the fact that in the following year the populations featured a relative balance of flowering for "male" and "female" individuals. Under the adverse conditions of drought "female" items get eliminated from the population first. Conclusions. A. dioica populations at the northern and southern boundaries of the range behave as amfimictic, while in the central part of the area – as facultatively apomictic. The ratio of flowering of "female" and "male" individuals in the populations of this species is essentially dependent on the latitude and weather conditions.